2021
DOI: 10.3390/antiox10050650
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Oleocanthal Supplementation Prevents Inflammation and Oxidative Stress in Collagen-Induced Arthritis in Mice

Abstract: Oleocanthal (OLE), a characteristic and exclusive secoiridoid of Oleoaceae family, is mainly found in extra virgin olive oil (EVOO). Previous studies have reported its antioxidant, anti-inflammatory, antimicrobial, anticancer and neuroprotective effects. Since the pathogenesis of rheumatoid arthritis (RA) involves inflammatory and oxidative components, this study was designed to evaluate the preventive role of dietary OLE-supplemented effects in collagen-induced arthritis (CIA) murine model. Animals were fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…In the present study, we reported that met-OLE suppressed MAPKs’ phosphorylation in a concentration-dependent manner. These results are in line with those from our previous studies, which reported that MAPKs’ activation was drastically inhibited by OLE in LPS -induced murine macrophages [ 14 ], as well as in the paws of arthritic animals fed with this EVOO phenol [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we reported that met-OLE suppressed MAPKs’ phosphorylation in a concentration-dependent manner. These results are in line with those from our previous studies, which reported that MAPKs’ activation was drastically inhibited by OLE in LPS -induced murine macrophages [ 14 ], as well as in the paws of arthritic animals fed with this EVOO phenol [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…OLE represents up to 10% of the total polyphenol content in EVOO (0.2–498 mg/kg) [ 12 ] and has received more scientific attention, due to its interesting biological activities, both within in vitro and in vivo systems, including anti-inflammatory, antioxidant, cardioprotective, chemopreventive and neuroprotective properties [ 10 , 13 ]. In fact, recently, we have reported the preventive role of dietary OLE-supplemented effects in a collagen-induced arthritis (CIA) murine model and the ability of OLE to diminish the acute inflammatory response in LPS-induced murine peritoneal macrophages [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups reported the anti-oxidant and anti-inflammatory activities of oleocanthal and oleuropein [30][31][32][33][34][35][36][37], while those of OLC are still poorly defined. Recently, it has been shown that OLC exerts anti-inflammatory effects in human adipocytes challenged with TNF-α, a prototypic inflammatory stimulus, which could aid to explain the cardiometabolic benefit of EVOO consumption [32].…”
Section: Introductionmentioning
confidence: 99%
“…Cruciferae) are distributed worldwide, and many of them have been traditionally used as anti-arthritic [ 9 ] and antirheumatic [ 10 ]. In this context, plants of genus Diplotaxis provided supporting evidence for this traditional use as they exhibited anti-inflammatory [ 11 , 12 , 13 ] and antioxidant/antiradical [ 13 , 14 , 15 ] activities since inflammation and oxidative stress are linked to inflammatory movement disorders, including rheumatoid arthritis [ 16 , 17 , 18 ]. Genus Diplotaxis includes edible and medicinal plants [ 12 , 19 , 20 ] of about 30 species, mainly distributed in Central Europe, the Mediterranean region [ 21 ], and Southwest Asia [ 22 ], including Saudi Arabia [ 23 ].…”
Section: Introductionmentioning
confidence: 99%